1978
DOI: 10.1093/ajcn/31.10.1831
|View full text |Cite
|
Sign up to set email alerts
|

Total parenteral nutrition in the management of acute renal failure

Abstract: Malnutrition is frequently present in patients with acute renal failure and may affect morbidity and mortality in this condition. When adequate nourishment cannot be given through the gastrointestinal tract, total parental nutrition with amino acids and hypertonic glucose may have beneficial results. Total parenteral nutrition has been reported to stabilize or reduce serum urea nitrogen, potassium and phosphorus levels, improve wound healing, enhance survival from acute renal failure, and possibly increase the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…However, nitrogen balance remains negative in all patients 2 suggesting that decreased protein synthesis is not the sole cause of loss of body nitrogen. Several studies have shown that proteinases participate in protein catabolism of patients with hypercatabolic ARF3-6.…”
Section: Introductionmentioning
confidence: 93%
“…However, nitrogen balance remains negative in all patients 2 suggesting that decreased protein synthesis is not the sole cause of loss of body nitrogen. Several studies have shown that proteinases participate in protein catabolism of patients with hypercatabolic ARF3-6.…”
Section: Introductionmentioning
confidence: 93%
“…An early study compared hypertonic glucose alone with a solution containing essential amino acids and demonstrated increased survival and return of renal func tion in the latter group [52], However, no significant dif ferences in survival, renal recovery, or laboratory evi dence of nitrogen balance were seen in several subsequent studies that examined modifications of the type (essential versus nonessential) and quantity of amino acid supple mentation provided [53][54][55]. These negative findings could be attributed to the overwhelming effects of severe underlying disease [56]; furthermore, each study had lim ited statistical power to detect intra-group differences due to small sample size (range: 6-45).…”
Section: Effects O F Peritoneal D Ialysis On N Utritionmentioning
confidence: 99%
“…[19] proposes a ratio of EAA to non-EAA of about 3:1 to 4:1. Generally, in hypercatabolic ARF, there seems to be an increased requirement for branched-chain amino acids [12], moreover, they are sup posed to have a pharmacologically anabolic effect [4,12,21], Therefore, Kopple and Cianciaruso [40] think that about 40% of the administered EAA should be provided as branched-chain amino acids. Perhaps, this regimen will provide better the requirement of amino acids in catabolic ARF with follow ing reduction of negative nitrogen balance; up to now, there are no controlled studies demonstrating this effect.…”
Section: Reduction Of Negative Nitrogen Balance As a Current Principlmentioning
confidence: 99%
“…In the early postaggressive phase, only 30% of infused lipid can be utilized for generation of energy, indicating that lipid emulsions are not a suit able source to fulfill energy demands in the early phase of illness [46], If the patient is on TPN for a longer period, lipid infusions are necessary in order to prevent essential fatty acid deficiency [46], The administration of 250-500 g of lipid emulsion at least twice weekly is generally recommended [40] with infusion in small doses due to the fact that lipid emulsions are composed primarily of triglycerides for which clearance is generally decreased in uremia [12]. Additionally, lipid emulsions have been reported to block the reticuloendothelial system, resulting in di minished resistance to infection and induc tion of dissiminated intravascular coagulopa thy [46], The daily vitamin requirement in ARF treated with TPN is not well defined and data have been derived predominantly based on studies of chronic uremia [40].…”
Section: Practical Implications For Nutritional Therapy In Arfmentioning
confidence: 99%
See 1 more Smart Citation